Australian orthopaedic surgery training: Australian Orthopaedic Association's strategic education review. Issue 6 (19th December 2019) - Incoll, Ian W.; Atkin, Jodie; Owen, John; Keane, Ally; Khorshid, Omar; Cosenza, Adrian; Frank, Jason
Abstract: Background: The Australian Orthopaedic Association (AOA) is the peak professional body for orthopaedic surgeons in Australia and is responsible for their training and continuing medical education. The 2012 AOA strategic education review employed a gap analysis to identify issues and generate a roadmap for the enhancement of AOA's education and training activities. This paper describes the process and outcomes of this review, which led to the 'AOA 21' Education Re‐design Project, and the review's relevance to surgical education in Australia. Methods: The AOA strategic education review was undertaken by international clinician education and orthopaedic experts, and involved AOA staff, fellows and trainee members throughout Australia. This review progressed through four phases: a review of current training; a global 'best‐practice' perspective; a set of aspirational goals; and a roadmap for implementation. Results: Seven key strengths (e.g. camaraderie in training and surgical skills teaching) and 15 challenges (e.g. 'non‐technical' skills teaching, subjective methods of decision making and inadequate assessment practices) were identified in the review stage. Sixteen major recommendations for improvements incorporating current or emerging world's best education practices were targeted in an 8‐year implementation framework. Conclusion: The AOA's strategic education review serves as a roadmap for other specialty training organizations to review their programmes and implement contemporary best practices in surgical training. The AOA 21 project has positioned orthopaedic surgery as a leader in competency‐based surgical education and training in Australia. Abstract : The Australian Orthopaedic Association's strategic education review of orthopaedic surgical training in Australia.